Adora Risk Identification of Tricyclic Antidepresant - Aydin, Macit; Yardan, Turker; Baydin, Ahmet; Genc, Selim (Duzce Univ, 2018)
Objective: Tricyclic antidepressant (TCA) poisonings can cause serious clinical outcome. The Antidepressant Overdose Risk Assessment (ADORA) criteria are used in the assessment of patients with TCA poisoning. However, the data about the benefits of these criteria in mortality and morbidity prediction in the clinical practice are insufficient. The aim of this study was to determine the relationship of ADORA criteria with clinical outcome. Methods: A total of 133 patients who admitted only with TCA poisoning at a university hospital emergency department. The patients were divided into high risk and low risk groups according to ADORA criteria. Results: The median age was 25 (range 18-55) years. Patients commonly used amitryptiline as TCA agent. According to risk classification; 59.4% of the patients were in high risk group. Most common symptom was mydriasis in study group; somnolence was more frequent in high risk group. The most common finding on electrocardiogram was the right axis deviation and the AVR was the R>S finding. The patients were discharged without any complications. As the number of ADORA positive risk scores increased, the length of hospitalization, QTc height and seizure frequency increased. Conclusion: The ADORA criteria is useful in assessment and clinical follow-up of TCA poisoning.
Keywords: ADORA; The Antidepressant Overdose Risk Assessment; Poisoning; Tricyclic Antidepressants